SOSIALISAI MENGENAI INTERVENSI PENDIDIKAN ANAK BERKESULITAN BELAJAR BAGI GURU SD NEGERI 02 CODO KECAMATAN WAJAK KABUPATEN MALANG - Ruth Rosalia Nababan; Hengky Triwijaya (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2022)
The aim of the Intervention Socialization for Children with Special Learning Difficulties at SDN 02 Codo, Wajak District, Malang Regency is to provide teachers with SDN 02 Codo, Wajak District, Malang Regency about intervention programs for children with special learning difficulties. The target of this program is SDN 02 Codo teachers in Codo Village, Wajak District, Malang Regency. The strategy for implementing the "Socialization of Intervention of Children with Special Learning Disabilities" activities in Codo Village, Wajak District, is as follows: (a) Observation; (b) Preparation; (c) Implementation; and (d) Post Implementation. The implementation of the "Socialization of Intervention for Children with Special Learning Difficulties" program at SDN 02 Codo, Wajak District, Malang Regency was realized on June 5 2013 in the teacher's room at SDN 02 Codo with 13 teachers participating. Achievement of results in this program is only 80%. The participants were very enthusiastic during the socialization activities but due to limited time so that the assistance to the teacher regarding how to intervene was not optimal, but from several responses from the teacher, the teacher understood the material enough and the teacher also felt helped by the module which contained intervention programs for children with special learning difficulties.